An exploratory study into the use of information technology as an important enabler of organisational differentiation in the financial sector - Casey, Mary-Ellen (School of Management Working Papers, 1995)
Organisations need to differentiate themselves from their competitors if they are to survive. This research project explores the role of information technology as an important enabler of organisational differentiation. Senior executives were interviewed from 9 New Zealand financial organisations to determine if information technology was an important enabler of organisational differentiation. No examples, where information technology was to used as an important enabler of organisational differentiation, were found.